2009
DOI: 10.1108/14777270910952243
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient satisfaction survey in a gastrointestinal endoscopy service

Abstract: PurposeThe principal aim of this study is to assess the determinants of patient satisfaction in a gastrointestinal (GI) endoscopy service.Design/methodology/approachA standardised questionnaire is the tool used to measure the perception of patient satisfaction. Questions were grouped by topic into the following sections: service choice, access, approach to the service, endoscopic procedures, staff caring, endoscopy facilities, histological biopsies, ticket payment, communication and information, therapeutical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The results of the current study are consistent with those of US and UK populations undergoing gastroscopy [22,23] and Canadian patients undergoing gastroscopy or colonoscopy [21]. By comparison, Scotto [26] surveyed patients undergoing gastroscopy or colonoscopy, finding associations between interactive factors with patient satisfaction including the caring nature of the staff and explanation of results but also environmental factors including hospital cleanliness and endoscopy area comfort. Del Rio [27] used a validated retrospective experiential questionnaire based on the GHAA in patients also undergoing gastroscopy or colonoscopy, and identifying waiting times for the appointment and explanations of the examination as important in determining patient satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the current study are consistent with those of US and UK populations undergoing gastroscopy [22,23] and Canadian patients undergoing gastroscopy or colonoscopy [21]. By comparison, Scotto [26] surveyed patients undergoing gastroscopy or colonoscopy, finding associations between interactive factors with patient satisfaction including the caring nature of the staff and explanation of results but also environmental factors including hospital cleanliness and endoscopy area comfort. Del Rio [27] used a validated retrospective experiential questionnaire based on the GHAA in patients also undergoing gastroscopy or colonoscopy, and identifying waiting times for the appointment and explanations of the examination as important in determining patient satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…The 202 respondents from the current study reflected a balanced distribution of patients across age, gender and educational level (demographic factors have been shown to influence responses,14 22 23 although principally satisfaction levels as opposed to the importance placed on specific aspects of care). The results of the ranking questionnaire suggested that patients considered ‘interactive’ factors with staff, for example, with the endoscopist and nurses/support staff, to be of greatest importance to achieving a satisfactory experience.…”
Section: Discussionmentioning
confidence: 92%
“…In both cases, patients noted the importance of the endoscopist's and nursing staff's personal manner and the endoscopist's technical skill, to their level of satisfaction with their healthcare experience, with lower levels of importance attributed to environmental factors 20 21. Scotto et al noted associations between interactive factors and patient satisfaction with gastroscopy including the caring nature of the staff and explanation of the results as well as environmental factors including hospital cleanliness and endoscopy area comfort22; however, the relative importance of these factors was not assessed. Del Río et al also used a validated postendoscopy questionnaire based on the GHAA in patients undergoing gastroscopy and/or colonoscopy and identified waiting times for the appointment and explanations of the examination24 as important in determining patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Study methodologies differed in terms of questionnaire format, timing of questionnaire completion and mode of questionnaire administration. Questionnaire formats included 5-point rating scales (20,22,25,27) and Likert scales (21,24,26,27), binary 'Yes/No' responses (20) and 100 mm visual analogue scales (23). In two studies (20,21), the degree of pain during the procedure was assessed using either a 4-or 7-point rating scale.…”
Section: Study Methodsmentioning
confidence: 99%
“…The timing of questionnaire completion differed across studies. In five studies (20,21,23,24,27), questionnaires were completed before discharge from the endoscopy units. In seven studies, they were completed within 24 h (21,23), three days (22), seven days (20), three weeks (26,27) or up to six months (25) following the procedure.…”
Section: Study Methodsmentioning
confidence: 99%